2020
DOI: 10.1007/s12517-020-06176-y
|View full text |Cite
|
Sign up to set email alerts
|

Sand failure: effect of biocide on the geomechanical properties of outcrop carbonate rock under static condition

Abstract: The effects of chemical interaction of a biocide with formation rocks on the rock geomechanical properties are examined. A combination of analytical tests (scanning electron microscopy/energy-dispersive X-ray analysis, X-ray powder diffraction and particle size distribution) and uniaxial compression test was used in this study. The particle size distribution in the effluent showed an increase in D50 with poor sorting for the chemically treated outcrop carbonate core samples. The XRPD shows evidence of altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the source of the reduction must be identified before any corrective measures can be taken. The reactive fluid flow momentum through a porous material is accountable for the heterogeneous geochemical reactions like precipitation and dissolution that occur at the rock minerals and the pore-fluids interface (Lamy- Chappuis et al 2014;Wuyep et al 2020). In other words, fluid flow can be described as a reactive transport system.…”
Section: Chemical Reaction (Dissolution-precipitation)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the source of the reduction must be identified before any corrective measures can be taken. The reactive fluid flow momentum through a porous material is accountable for the heterogeneous geochemical reactions like precipitation and dissolution that occur at the rock minerals and the pore-fluids interface (Lamy- Chappuis et al 2014;Wuyep et al 2020). In other words, fluid flow can be described as a reactive transport system.…”
Section: Chemical Reaction (Dissolution-precipitation)mentioning
confidence: 99%
“…Reservoirs formation experiences numerous fluid-rock interactions; thus, it is crucial to identify the specific geochemical reactions and processes governing the evolution of porosity and permeability (Yang et al 2017a(Yang et al , 2017b(Yang et al , 2017c. Investigations have shown that various chemicals would have different properties, which would have varying influences on the strength of the reservoir formation when they are injected (Wuyep et al 2020). Oluyemi 2014aOluyemi , 2014b) experimentally investigated the sanding potential of using scale inhibitors (PTEMP) on a clashach reservoir rock under dynamic condition.…”
Section: Introductionmentioning
confidence: 99%